Kalkulasi Penghematan Energi dan Biaya untuk Beban Penerangan dan Pendingin di Gedung ADB CRM Pt. Krakatau Steel (Persero Tbk.) - Muhamad Otong; Yudha Iskana (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2020)
The use of electric power in modern times has become a very vital thing. Electrical energy is a necessity in various activities. The need for electrical energy is increasing from time to time, especially large industries such as PT. Krakatau Steel (Persero Tbk.). the amount of electricity consumption causes electricity costs to become large. Then the office relocation program was launched to reduce electricity consumption, especially in the Administration Cold Rolling Mill Building PT. Krakatau Steel (Persero Tbk.). Retrieval of data Savings obtained from the relocation of this office amounted to 365,523.8 kWh / year, with a saved cost of Rp 439,396,208 / year. The average Energy Use Intensity for each non-AC room of the ADB CRM building is 12.78 / m2 / year with an area of 531.75 m2. The average Energy Use Intensity for each air-conditioned room in the ADB CRM building is 161.21 / m2 / year with an area of 2180.05 m2. When compared with the ECI standard, the EUI value of non-AC and air-conditioned rooms is still in the efficient category. EUI values that fall into the category of waste are non-AC rooms in the Accounting Sub-Directorate. The EUI values included in the waste category are air-conditioned rooms in the Financial Accounting Division 2, Management Accounting, SABM Sub-Directorate, and the SCI Division. Each room has a value of IKE 194.59 kWh / m2 / yr, 193.42 kWh / m2 / yr, 194.85 kWh / m2 / yr, and 218.15 kWh / m2 / yr.